1997
DOI: 10.1177/070674379704200208
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Aspects of Coronary Artery Disease Related to Military Patients

Abstract: Most studies of the psychosocial impact of CAD are based on civilian populations. A review of available studies suggests that little is known about how military patients adapt to CAD, particularly with regard to symptoms of depression and anxiety, social impairment, and rates of return to work. Studies in this area are needed regarding the psychosocial aspects of CAD in military populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Coronary artery disease (CAD) is the dominant cause of morbidity, mortality and impaired quality of life. Following major events, patients with CAD experience psychological problems such as anxiety, depression and significant increase in stress level . Going through such psychological status could put patients at increased risk of re‐infarction, malignant arrhythmias, heart failure and sudden death …”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery disease (CAD) is the dominant cause of morbidity, mortality and impaired quality of life. Following major events, patients with CAD experience psychological problems such as anxiety, depression and significant increase in stress level . Going through such psychological status could put patients at increased risk of re‐infarction, malignant arrhythmias, heart failure and sudden death …”
Section: Introductionmentioning
confidence: 99%
“…However, studies of the long-term cardiovascular consequences of combat stress are limited, and inconclusive. (3,11) We report on the association between exposure to military combat and coronary heart disease (CHD) and ischemic stroke (IS) in a community-based sample of men serving during the eras of World War II, the Korean War and the Vietnam Conflict.…”
Section: Introductionmentioning
confidence: 99%
“…Our review ofthe literature on psychosocial aspects of CAD related to military patients revealed that little is known about howmilitary patients adapt to CAD, particularly with respect to symptoms of depression and anxiety, social impairment, and rates ofreturn to work. 17 Thepurposeof this study was to determine how a group of military patients with stable CAD have adapted physically and psychosocially, and to compare results with those from a group of healthy military men and a group of male civilian patients with stable CAD. Because almost all patients with CAD in the Canadian Forces are male, we considered only men.…”
Section: mentioning
confidence: 99%